Civilians in the Line of Fire in the Light of Catholic Social Teaching - Michael, Biju (Annales. Etyka w Życiu Gospodarczym, 2015)
In our world today, afflicted by wars between States, by conflict between groups within States, and by the scourge of terrorism, civilians constitute the ‘vast majority of casualties in situations of armed conflict’ (UN Security Council, Resolution 1894, 2009). Civilian victims of documented and un-documented armed conflicts and their destructive consequences run in the millions. An overwhelming majority of the dead, injured, disabled are civilians and damages caused by armed conflicts primarily affect the civilian infrastructure and the basic resources of subsistence of entire populations. Civilians today are in the line of fire not only as a side effect of war. Increasingly, they are becoming the prime and intentional targets of combatants and armed elements. ‘Political and military designs supersede basic respect for the dignity and rights of persons and communities’ (Migliore 2009) and civilians are becoming deliberate targets and means for achieving political or military gains. They are even being used as a human shield for armed advancement. The menace of civilian deaths in the line of fire is of utmost concern for all humanity, for all religions, and for Christianity. Among the foundational teachings on which the Catholic perspective to this important issue of placing civilians in the line of fire is based, we can identify three core beliefs: a) all human beings are equal in dignity and their life is sacred; b) the right and duty to defend the life and common good from unjust aggressors; c) the permanent validity of the moral law forbidding murder even in the context of armed conflicts. After considering these the paper studies some of the ways in which the Catholic Church responds to the situation of civilians caught in the line of fire.